2020
DOI: 10.1140/epjc/s10052-020-7932-8
|View full text |Cite
|
Sign up to set email alerts
|

Wormhole solutions with a polynomial equation-of-state and minimal violation of the null energy condition

Abstract: This paper discusses wormholes supported by general equation-of-state , resulting in a significant combination of the linear equation-of-state and some other models. Wormhole with a quadratic equation-of-state is studied as a particular example. It is shown that the violation of null energy condition is restricted to some regions in the vicinity of the throat. The combination of barotropic and polytropic equation-of-state has been studied. We consider fluid near the wormhole throat in an exotic regime which at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
(125 reference statements)
0
18
0
Order By: Relevance
“…This information allows us to close the θ -system determining the full θ μν tensor (and, consequently, the full energy-momentum tensor of the solution) and the decoupler function, f (r ), therefore closing the problem at least from a mathematical point of view. This approach motivates and also allows to support the idea that these type of solutions can be constituted by the dark sector, which dominates our Universe [11][12][13][14][15][16][17][18][19][41][42][43]. Even more, it provides a possible interpretation of the contribution introduced by MGD.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This information allows us to close the θ -system determining the full θ μν tensor (and, consequently, the full energy-momentum tensor of the solution) and the decoupler function, f (r ), therefore closing the problem at least from a mathematical point of view. This approach motivates and also allows to support the idea that these type of solutions can be constituted by the dark sector, which dominates our Universe [11][12][13][14][15][16][17][18][19][41][42][43]. Even more, it provides a possible interpretation of the contribution introduced by MGD.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, wormhole solutions with other type of symmetries have been investigated in [37][38][39] and also the possibility to obtain a traversable Schwarzschild-like wormhole has been considered [40]. Furthermore, recently [41] was studied and analyzed the behavior of wormhole structures in the realm of dark matter profiles, dark matter Bose-Einstein condensates [42] and non-linear equation of state [43], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The general constraints on these functions have been discussed by Morris and Thorne in [3]. It is clear that if b(r) and φ(r) tend to zero the metric (7) reduces to a flat FLRW metric, and as R(t) → constant the static Morris-Thorne wormhole is recovered. In the model herein, we seek a way to determine the shape function b(r) and the scale factor R(t) in order to construct dynamical wormhole configurations.…”
Section: Action and Field Equationsmentioning
confidence: 99%
“…For instance, in [6], a particular class of spacetime geometries admitting a traversable wormhole has been constructed using arbitrarily small quantities of exotic matter. In [7], it is shown that considering a general equation of state for the fluid profiles can act in favor of minimal usage of exotic matter. However, generalizing the matter sector may not necessarily guarantee obtaining a setting for nonexotic wormhole geometries [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this realm, the exotic matter can be confined to the shell. Wormhole with variable EoS [7] and polynomial EoS [8] are presented in the literature. In this class of solutions, the violation of NEC is restricted in some regions in the vicinity of the throat.…”
Section: Introductionmentioning
confidence: 99%